2022
DOI: 10.3233/adr-210060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Receptor Substrate-1 Gene Polymorphism (rs1801278) with Alzheimer’s Disease

Abstract: Background: Alzheimer’s disease (AD) is the most common form of dementia. AD is also the leading cause of morbidity and mortality due to dementia worldwide. It has been shown that AD is associated with type 2 diabetes mellitus (T2DM) and brain insulin resistance. Rs1801278 is a polymorphism in insulin receptor substrate-1 (IRS-1) gene which changes the amino acid Arg972. This polymorphism has been found to be associated with susceptibility to AD in some populations. Objective: In the present study, our aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Conclusion: “The results suggested that the restoration of insulin activity represents a promising therapeutic target for improve cognitive decline in AD”. Reference: Niyasti et al 13 ; Type of study: Case-control study; Objective: “Polymerase chain reaction was performed to amplify a DNA segment of 263 base-pair length containing the single nucleotide polymorphism”; Participants: 150 patients with late-onset AD and 150 unrelated healthy controls; Diagnosis method of AD: National Institute on Aging and Alzheimer’s Association; Diagnosis criteria of BIR: Rs1801278 polymorphism in the insulin receptor substrate-1; Covariates studied: Age, sex, genotype. Conclusion: “Association of Insulin Receptor Substrate-1 Gene Polymorphism (rs1801278) present at the BIR is significantly associated with the risk of developing AD”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusion: “The results suggested that the restoration of insulin activity represents a promising therapeutic target for improve cognitive decline in AD”. Reference: Niyasti et al 13 ; Type of study: Case-control study; Objective: “Polymerase chain reaction was performed to amplify a DNA segment of 263 base-pair length containing the single nucleotide polymorphism”; Participants: 150 patients with late-onset AD and 150 unrelated healthy controls; Diagnosis method of AD: National Institute on Aging and Alzheimer’s Association; Diagnosis criteria of BIR: Rs1801278 polymorphism in the insulin receptor substrate-1; Covariates studied: Age, sex, genotype. Conclusion: “Association of Insulin Receptor Substrate-1 Gene Polymorphism (rs1801278) present at the BIR is significantly associated with the risk of developing AD”.…”
Section: Resultsmentioning
confidence: 99%
“… Reference Year Design Sample size Objective Conclusions Risk of bias as per QUADAS-2 Su et al 12 2016 Case-control 222 “Longitudinal study for an average of 35 months to assess cognitive decline over time” “The results suggested that the restoration of insulin activity represents a promising therapeutic target for improve cognitive decline in AD”. Good-quality Niyasti et al 13 2022 Case-control 300 “Polymerase chain reaction was performed to amplify a DNA segment of 263 base-pair length containing the single nucleotide polymorphism” “Association of Insulin Receptor Substrate-1 Gene Polymorphism (rs1801278) present at the BIR is significantly associated with the risk of developing AD” Good-quality van der Velpen et al 14 2019 Case-control 74 “Paired plasma and cerebrospinal fluid samples” “The study showed the translational potential of the pathway quantitative to assess central nervous system metabolic defects which are part of the AD pathophysiology”. Low-moderate Andalib et al 15 2019 Case-control 243 “To test the hypothesis of association of late onset Alzheimer’s disease (AD) with DM2 in an Iranian population” “The evidence from the present study suggested that DM2 was associated with AD in an Iranian population” Good-quality ...…”
Section: Resultsmentioning
confidence: 99%